Short arc discharge lamp
The ceramic-coated anode with controlled groove depth and thickness ratio enhances heat dissipation, addressing overheating issues and extending the lifespan of short-arc discharge lamps by maintaining high illuminance.
Patent Information
- Application Number
- JP2021108564
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-06-30
AI Technical Summary
Existing short-arc discharge lamps face issues with ineffective heat dissipation, leading to electrode material evaporation and reduced light transmittance due to the anode overheating, which affects the lamp's lifespan.
The lamp features a ceramic-coated anode with a cylindrical outer surface having circumferential grooves and a specific ratio of groove depth to coating thickness, enhancing heat dissipation and suppressing electrode material evaporation.
The improved heat dissipation properties extend the lamp's lifespan by maintaining high illuminance levels, with an illuminance maintenance rate exceeding 80% after 500 hours of use.
Smart Images

Figure 0007615917000002 
Figure 0007615917000003 
Figure 0007615917000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a short arc type discharge lamp. [Background technology]
[0002] Short arc type discharge lamps (hereinafter simply referred to as "lamps") are widely used as light sources for exposure devices used in the manufacturing process of semiconductor devices or liquid crystal display devices. This short arc type discharge lamp is configured such that an anode and a cathode are arranged opposite each other in an arc tube, and a luminous substance such as mercury or xenon gas is sealed in the arc tube.
[0003] In such short arc type discharge lamps, the anode is subjected to a high thermal load during lighting, which causes the electrode material to evaporate due to overheating of the anode, and this evaporated material adheres to the inner wall of the arc tube, causing the arc tube to blacken. When the arc tube blackens, the light transmittance of the arc tube decreases.
[0004] To solve these problems, a technology is known in which a heat dissipation layer is formed on the surface of the electrode to suppress the temperature rise of the electrode. Patent document 1 listed below discloses a lamp in which a heat dissipation layer containing at least one type of metal oxide is formed on the outer surface of the anode. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2004-259639 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the lamp described in Patent Document 1, in order to improve the adhesive strength of the heat dissipation layer, an uneven surface with Rmax of 10 μm or more is formed on the surface of the anode, and a heat dissipation layer is provided on that surface. An example is disclosed in which the surface layer of the heat dissipation layer has Rmax of 2 μm to 100 μm.
[0007] In order to improve heat dissipation, it is desirable to make the surface of the heat dissipation layer uneven. However, even if the surface of the anode is uneven, depending on the thickness of the heat dissipation layer formed thereon, unevenness (unevenness reflecting the uneven shape of the anode surface) may not be formed on the surface of the heat dissipation layer, and heat may not be dissipated effectively.
[0008] The present invention has been made in consideration of the above problems, and has an object to provide a long-life short arc type discharge lamp that has excellent heat dissipation properties and in which evaporation of electrode material during lamp operation is suppressed. [Means for solving the problem]
[0009] The short arc type discharge lamp according to the present invention comprises an arc tube and a pair of electrodes disposed opposite each other inside the arc tube, At least one of the pair of electrodes has a cylindrical outer circumferential surface, the outer circumferential surface has an uneven structure in which a plurality of circumferential grooves extending in a circumferential direction are arranged in an axial direction, and a first coating including a ceramic is formed on an uneven surface of the uneven structure, When the groove depth of the circumferential groove is a (μm) and the distance from the groove bottom of the circumferential groove to the surface of the first coating is b (μm), the relationship of the following formula (1) is satisfied. 1≦b / a≦4 (1)
[0010] According to this configuration, the surface of the first coating is formed with unevenness reflecting the uneven shape of the uneven structure, and the unevenness improves heat dissipation. As a result, the short arc type discharge lamp of the present invention has excellent heat dissipation properties of the electrodes, which suppresses evaporation of the electrode material during lamp operation and extends the life of the lamp.
[0011] In the short arc type discharge lamp of the present invention, the ceramic may contain at least one of a metal oxide, a metal carbide, a metal boride, a metal silicide, and a metal nitride.
[0012] In the short arc type discharge lamp of the present invention, the ceramic may be mainly composed of zirconium oxide. In this specification, the term "main component" is used to mean the component that has the largest content by mass.
[0013] According to these configurations, the first coating can exhibit excellent emissivity as a high emissivity coating.
[0014] In the short arc type discharge lamp of the present invention, the one electrode has a front electrode portion whose outer diameter becomes smaller toward a tip thereof, A second coating containing a metal having a higher melting point than the ceramic may be formed on a surface of the front portion of the electrode.
[0015] In the short arc type discharge lamp of the present invention, the one electrode has a front electrode portion whose outer diameter becomes smaller toward its tip, The surface of the front part of the electrode may be micro-grooved.
[0016] These configurations can further improve the heat dissipation properties of the electrodes. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is an explanatory diagram showing the configuration of a short arc type discharge lamp according to an embodiment of the present invention; [Diagram 2] An enlarged view of the II region of the short arc type discharge lamp shown in FIG. [Diagram 3] FIG. 3 is an enlarged cross-sectional view of the region III shown in FIG. [Figure 4] Enlarged cross-sectional view when the first coating is thick [Diagram 5] Traced SEM image of the cross section of the anode [Figure 6] Traced SEM image of the cross section of the anode [Figure 7] 1 is a front view of an anode according to another embodiment; [Figure 8] 1 is a front view of an anode according to another embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The following description will be made with reference to the drawings, which are schematic diagrams of the short arc type discharge lamp according to the present invention. The dimensional ratios in the drawings do not necessarily match the actual dimensional ratios, and the dimensional ratios between the drawings do not necessarily match.
[0019] In the following, the XYZ coordinate system will be appropriately referenced. In addition, in this specification, when expressing a direction, if a positive or negative direction is to be distinguished, it is described with a positive or negative sign, such as "+X direction" and "-X direction". In addition, when expressing a direction without distinguishing between positive and negative directions, it is simply described as "X direction". In other words, in this specification, when simply described as "X direction", both "+X direction" and "-X direction" are included. The same applies to the Y direction and the Z direction.
[0020] 1 is an explanatory diagram showing the configuration of a short arc type discharge lamp according to this embodiment. A short arc type discharge lamp 1 (hereinafter referred to as "lamp 1") comprises an arc tube 2, and an anode 3 and a cathode 4 arranged opposite each other inside the arc tube 2. The anode 3 and the cathode 4 are each supported by a lead rod 5.
[0021] The lamp 1 of this embodiment is a large lamp used in an exposure device that is used in the manufacturing process of a semiconductor device or a liquid crystal display device, and has a rated power of, for example, 2 kW to 35 kW.
[0022] The arc tube 2 is formed by inflating the center of a glass tube. The arc tube 2 is a region of the glass tube whose inside diameter increases from both ends in the X direction toward the center. The outer shape of the arc tube 2 is a sphere or an ellipsoid.
[0023] The arc tube 2 has a pair of sealed tube portions 21 that extend continuously in opposite directions from both ends of the arc tube 2 in the X direction. The arc tube 2 is integrally formed with the sealed tube portions 21 from, for example, quartz glass. The central axes of the pair of sealed tube portions 21 overlap each other and are indicated by axis X1 in FIG.
[0024] A light-emitting space S1 is formed inside the light-emitting tube 2. A light-emitting material such as mercury is enclosed in the light-emitting space S1.
[0025] Inside the arc tube 2, an anode 3 and a cathode 4 are arranged facing each other in the X direction. In this embodiment, the short arc type discharge lamp is a discharge lamp in which the anode 3 and the cathode 4 are arranged facing each other with a gap of 40 mm or less (the value at room temperature without thermal expansion). In this embodiment, the material of the anode 3 is tungsten, and the material of the cathode 4 is thoriated tungsten.
[0026] The lead rod 5 is connected to the anode 3 and the cathode 4, and extends in the X direction inside the sealed tube portion 21. The anode 3 and the cathode 4 are fixed to the tip of the lead rod 5. The central axis of the lead rod 5 may overlap with the axis X1. The lead rod 5 is made of a material containing a high melting point metal, for example, tungsten.
[0027] The base 8 covers the side of the sealed tube portion 21 that faces away from the anode 3 and the cathode 4. The base 8 is electrically connected to the lead rod 5.
[0028] Fig. 2 is an enlarged view of a region II of the lamp 1 shown in Fig. 1. On part of the surface of the anode 3, a first coating 6 containing ceramics is formed.
[0029] The anode 3 has a cylindrical main body 3a centered on the axis X1, and a front electrode portion 3b whose outer diameter decreases toward the tip (toward the cathode 4). The first coating 6 is formed on the cylindrical outer circumferential surface of the main body 3a.
[0030] Important factors to consider in selecting the material for first coating 6 include melting point, vapor pressure, emissivity, and thermal expansion coefficient. In order to lower the temperature of anode 3, first coating 6 is preferably made of a material with high emissivity so as to increase the amount of heat dissipation.
[0031] The first coating 6 includes ceramics. The ceramics include at least one of metal oxide, metal carbide, metal boride, metal silicide, and metal nitride. The material of the first coating 6 is preferably a material having a melting point of 2000°C or higher, such as aluminum oxide (Al2O3), zirconium oxide (ZrO2), zirconium carbide (ZrC), zirconium boride (ZrB2), tantalum silicide (TaSi2), and zirconium nitride (ZrN).
[0032] 3 is an enlarged cross-sectional view of the region III shown in FIG. 2. As shown in FIG. 3, an uneven structure 30 is provided on the outer peripheral surface of the main body 3a of the anode 3. The uneven structure 30 is configured by arranging a plurality of circumferential grooves 31 extending in the circumferential direction of the main body 3a in the axial direction (X direction). Such circumferential grooves 31 can be formed, for example, by lathe processing. When the circumferential grooves 31 are formed by lathe processing, a plurality of circumferential grooves 31 for one revolution may be arranged independently in the axial direction, or a plurality of circumferential grooves 31 may be spirally connected to form a single spiral groove as a whole.
[0033] A first coating 6 is formed on the uneven surface of the uneven structure 30. A surface 6a of the first coating 6 has unevenness formed thereon that reflects the uneven shape of the uneven structure 30. Since the surface 6a of the first coating 6 has unevenness formed thereon that reflects the uneven shape of the uneven structure 30, the unevenness improves heat dissipation properties.
[0034] The unevenness appearing on the surface 6a of the first coating 6 can be formed by controlling the thickness of the first coating 6. Fig. 4 is an enlarged cross-sectional view of a case where a first coating 6 thicker than that shown in Fig. 3 is formed. As shown in Fig. 4, when the thickness of the first coating 6 is thick, unevenness reflecting the uneven shape of the uneven structure 30 is not formed on the surface 6a, or even if it is formed, the unevenness is small.
[0035] The inventors have found through extensive research that in order to form unevenness on the surface 6a of the first coating 6 that reflects the uneven shape of the uneven structure 30 formed on the surface of the anode 3, it is necessary to adjust the thickness of the first coating 6 so as to satisfy the relationship 1≦b / a≦4, where a (μm) is the groove depth of the circumferential groove 31 and b (μm) is the distance from the groove bottom 311 of the circumferential groove 31 to the surface 6a of the first coating 6. The distance b can also be said to be the thickness of the first coating 6 at the groove bottom 311 of the circumferential groove 31.
[0036] If b / a is smaller than 1, the thickness of the first coating 6 is too thin, which may expose the peaks of the uneven structure 30. On the other hand, if b / a is larger than 4, the thickness of the first coating 6 is too thick, and unevenness reflecting the uneven shape of the uneven structure 30 is not formed on the surface 6a of the first coating 6, or even if it is formed, the unevenness is small, and the effect of improving heat dissipation is not obtained very much.
[0037] The groove depth a of the circumferential groove 31 is preferably, for example, 10 μm to 100 μm. If the groove depth a is less than 10 μm, irregularities are unlikely to be formed on the surface 6a of the first coating 6. If the groove depth a is more than 100 μm, it is unlikely that the first coating 6 will be formed in the circumferential groove 31.
[0038] The unevenness of the surface 6a has a height difference of 5 μm or more, and preferably 10 μm or more. If the height difference is less than 5 μm, it is difficult to obtain the effect of improving heat dissipation.
[0039] The thickness of the first coating 6 is preferably, for example, 10 μm or more. If the thickness of the coating 6 is thin, sufficient emissivity cannot be obtained. In order to appropriately form unevenness on the surface 6a, the thickness of the first coating 6 is preferably 100 μm or less, and more preferably 30 μm or less.
[0040] The first coating 6 is formed, for example, by dispersing particles of the material that constitutes the coating 6 (e.g., zirconium oxide particles having a particle size of 10 μm or less) in a solvent (e.g., a solvent consisting of nitrocellulose and butyl acetate), applying the resulting solution to the outer peripheral surface of the main body 3a of the anode 3 with a brush, drying the solution at 150°C for 30 minutes, and then performing a heat treatment at 1900°C for 120 minutes in a vacuum atmosphere.
[0041] 5 and 6 are traced SEM images of the cross section of the anode 3. Such SEM images of the cross section of the anode 3 are obtained by first making a cut in the anode 3 with a grinder (blade), fracturing the anode 3 starting from the cut, and observing the fracture surface with a scanning electron microscope (SEM). The thickness of the first coating 6 can be measured with measurement software attached to the SEM.
[0042] FIG. 5 is a trace of an SEM image when the groove depth a of the circumferential groove 31 is 30 μm, and the distance b from the groove bottom 311 of the circumferential groove 31 to the surface 6a of the first coating 6 is 50 μm, i.e., when b / a is about 1.66. FIG. 6 is a trace of an SEM image when the groove depth a of the circumferential groove 31 is 30 μm, and the distance b from the groove bottom 311 of the circumferential groove 31 to the surface 6a of the first coating 6 is 150 μm, i.e., when b / a is 5. In the example shown in FIG. 5, unevenness reflecting the uneven shape of the uneven structure 30 is formed on the surface 6a of the first coating 6. On the other hand, in the example shown in FIG. 6, almost no unevenness reflecting the uneven shape of the uneven structure 30 is formed on the surface 6a of the first coating 6.
[0043] The electrode front portion 3b of the anode 3 may have any shape as long as the outer diameter decreases toward the tip, and does not have to be a truncated cone shape in which the outer diameter decreases at a constant rate toward the tip as shown in Fig. 2. For example, as shown in Fig. 7, the outer peripheral surface of the electrode front portion 3b may be configured to have a cross-sectional shape that is curved such that the rate at which the outer diameter decreases toward the tip changes.
[0044] A second coating 7 containing a metal with a higher melting point than ceramics may be formed on the surface of the electrode front portion 3b as shown in Fig. 8. The second coating 7 containing a metal with a higher melting point than ceramics has higher heat resistance than ceramics, so there is no risk of it peeling off when the lamp is turned on. By providing this second coating 7, it is possible to further improve heat dissipation.
[0045] The metal having a higher melting point than ceramics is, for example, tungsten. The second coating 7 is formed, for example, by dispersing tungsten particles in a solvent, applying the solvent to the outer peripheral surface of the electrode front portion 3b of the anode 3 with a brush, and sintering the dispersion.
[0046] Moreover, instead of forming the second coating 7, the surface of the electrode front portion 3b may be subjected to microgroove processing. By performing microgroove processing, the heat dissipation property can be further improved. The microgroove processing can be performed by a laser processing machine. For example, the microgroove is formed to a depth of 650 μm and a pitch of 195 μm.
[0047] Although the embodiments of the present invention have been described above based on the drawings, the specific configuration should not be considered to be limited to these embodiments. The scope of the present invention is indicated not only by the description of the above embodiments but also by the claims, and further includes all modifications within the meaning and scope of the claims.
[0048] The structures employed in the above-described embodiments can be employed in any other embodiment. The specific configurations of each part are not limited to the above-described embodiments, and various modifications are possible without departing from the spirit of the present invention. Furthermore, one or more of the configurations, methods, etc. relating to the various modified examples described below may be arbitrarily selected and employed in the configurations, methods, etc. relating to the above-described embodiments.
[0049] In the above embodiment, the first coating 6 is provided only on the outer peripheral surface of the anode 3. However, the first coating 6 may also be provided on the outer peripheral surface of the cathode 4, or the first coating 6 may be provided only on the outer peripheral surface of the cathode 4 without providing the first coating 6 on the outer peripheral surface of the anode 3. EXAMPLES
[0050] Examples that concretely illustrate the configuration and effects of the present invention will be described below.
[0051] A plurality of anodes 3 were produced in which the groove depth (a) of the circumferential groove 31 and the thickness (b) of the first coating 6 were changed as shown in Table 1. The circumferential groove 31 was formed by lathe processing. The groove depth of the circumferential groove 31 can be adjusted by changing the processing conditions of the lathe processing. The first coating 6 was formed as follows. Zirconium oxide particles having a particle size of 10 μm or less were added to a solvent consisting of nitrocellulose and butyl acetate, and mixed well, and then applied to the outer circumferential surface of the anode 3 with a brush. Then, after drying at 150° C. for 30 minutes, heat treatment was performed at 1900° C. for 120 minutes in a vacuum atmosphere. The thickness of the first coating 6 can be adjusted by changing the viscosity of the solvent in which the zirconium oxide particles are dispersed.
[0052] The lamps incorporating the anodes 3 made with different specifications were lit for 500 hours at a rated power of 2 kW (voltage 25 V, current 80 A), and the illuminance maintenance rate was evaluated. The evaluation results are shown in Table 1.
[0053] The illuminance maintenance rate was determined by first measuring the illuminance at the start of lighting using a photodetector sensitive to a wavelength of 365 nm, then measuring the illuminance after 500 hours of continuous lighting at rated power, and calculating the ratio to the initial illuminance.
[0054] The specifications common to all the tested lamps are as follows: [Light emitting tube] Material: Quartz glass, Total length: 70mm Maximum diameter: φ55mm Content: 2.5mg / cc mercury Interelectrode distance: 5mm [anode] Material: Tungsten Length: 30mm Body diameter: φ20mm [cathode] Material: Thoriated tungsten Length: 20mm Body diameter: φ6mm
[0055] [Table 1]
[0056] As shown in Table 1, when b / a was 0.8 and 5, the illuminance maintenance rate after 500 hours of lighting was less than 80%, regardless of the value of a. On the other hand, when b / a was between 1 and 4, the illuminance maintenance rate exceeded 80%, regardless of the value of a.
[0057] When b / a is in the range of 1 to 4, the heat dissipation of the anode 3 is high and the amount of evaporation of the electrode material is reduced, resulting in a high illuminance maintenance rate. Moreover, when b / a is in the range of 1 to 2, the effect is even greater (90% or more). [Explanation of symbols]
[0058] 1: Short arc type discharge lamp (lamp) 2: Light emitting tube 3: Anode 3a: Main body 3b: Electrode front part 4 :Cathode 6: First coating 6a: Surface of the first coating 7: Second coating 30: Uneven structure 31: Circumferential groove 311: Bottom of circumferential groove a: Circumferential groove depth b: Distance from the bottom of the circumferential groove to the surface of the first coating
Claims
1. A light emitting tube and a pair of electrodes disposed opposite each other inside the light emitting tube, At least one of the pair of electrodes has a cylindrical outer circumferential surface, the outer circumferential surface has an uneven structure in which a plurality of circumferential grooves extending in a circumferential direction are arranged in an axial direction, and a first coating including a ceramic is formed on an uneven surface of the uneven structure, When the groove depth of the circumferential groove is a (μm) and the distance from the groove bottom of the circumferential groove to the surface of the first coating is b (μm), the relationship of the following formula (1) is satisfied, A short arc type discharge lamp, wherein the unevenness on the surface of the first coating has a height difference of 5 μm or more. 1≦b / a≦4 (1)
2. 2. The short arc type discharge lamp according to claim 1, wherein the ceramic includes at least one of a metal oxide, a metal carbide, a metal boride, a metal silicide, and a metal nitride.
3. 2. The short arc type discharge lamp according to claim 1, wherein said ceramics is composed mainly of zirconium oxide.
4. the one electrode has a front electrode portion whose outer diameter decreases toward its tip, 2. The short arc type discharge lamp according to claim 1, wherein a second coating containing a metal having a higher melting point than said ceramic is formed on a surface of said front portion of said electrode.
5. the one electrode has a front electrode portion whose outer diameter decreases toward its tip, 2. The short arc type discharge lamp according to claim 1, wherein the surface of the front part of the electrode is micro-grooved.
Citation Information
Patent Citations
Discharge lamp and its electrode structure
JP2004259639A
Discharge lamp with coated electrodes
JP2012527066A
Discharge lamp
JP2017069078A
Short arc type discharge lamp
JP2017111995A
Short arc discharge lamp
WO2021070459A1